Multilevel citizenship - Maas, Willem, 1972- (Democracy, citizenship, and constitutionalism., 2013)
This book challenges the dominant conception of citizenship as legal and political equality within a sovereign state, demonstrates how citizenship is constructed by political and legal practices, and explores alternative forms of membership in substate, suprastate, and nonstate political communities.